2011
DOI: 10.1111/j.1600-0897.2011.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Treg Cell Population Alterations in the Peripheral Blood of Patients Treated Surgically for Ovarian Cancer - A Preliminary Report

Abstract: It would seem that the alteration in the Treg cell subpopulation could be a key factor in determining the status of the tumour microenvironment. Most likely, it could provide information about whether the proper level of anti-cancer immune response could be restored. The possibility of restoring the immune response may directly correspond to the degree of radicalism of the surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
(37 reference statements)
2
15
0
1
Order By: Relevance
“…Statistically significant decreases of the percentage of Foxp3+CD4+CD25+ lymphocytes within the population of CD4+CD25+ lymphocytes and within the population of CD4+ T lymphocytes were observed following the surgical treatment. A similar observation was noted in ovarian cancer, where the percentages of FOXP3+ cells in the subpopulation of CD4+ T lymphocytes found in the peripheral blood of the patients before the surgical procedure were statistically significantly higher than those observed in the peripheral blood of the same patients after the surgical procedure [27]. The suppressive microenvironment in endometrial cancer is thus created by the recruitment of Treg cells into the tumour and its stroma and leads to an increase of the percentage of Treg cell population in the blood serum observed in various cancer patients [7,8].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Statistically significant decreases of the percentage of Foxp3+CD4+CD25+ lymphocytes within the population of CD4+CD25+ lymphocytes and within the population of CD4+ T lymphocytes were observed following the surgical treatment. A similar observation was noted in ovarian cancer, where the percentages of FOXP3+ cells in the subpopulation of CD4+ T lymphocytes found in the peripheral blood of the patients before the surgical procedure were statistically significantly higher than those observed in the peripheral blood of the same patients after the surgical procedure [27]. The suppressive microenvironment in endometrial cancer is thus created by the recruitment of Treg cells into the tumour and its stroma and leads to an increase of the percentage of Treg cell population in the blood serum observed in various cancer patients [7,8].…”
Section: Discussionsupporting
confidence: 58%
“…The malignant neoplasm destroys, therefore, the host immune response, and the surgical treatment aims to remove the tumour mass radically and to restore the immune response. It was demonstrated that when the degree of surgery radicalism increases the possibility of restoring the immune function also increases [25][26][27]. There is no efficient method for the evaluation of surgical treatment radicalism.…”
Section: Introductionmentioning
confidence: 99%
“…Patients and experimental models with cancer showed that Treg cells down-regulated the activity of effector function against tumors, resulting in T-cell dysfunction in cancerbearing hosts (Weiss et al, 2012;Sakuishi et al, 2013). An increased population of Treg cells was reported in patients with ovarian cancer (Wicherek et al, 2011), lung cancer (Erfani et al, 2012), and breast cancer (Decker et al, 2012). However, there are no previous reports describing Treg cells in gastric cancer.…”
Section: Introductionmentioning
confidence: 80%
“…Elevated Treg cell percentage have been already reported in breast, colorectal and ovarian cancers, as well as brain tumors, hepatocellular carcinoma (HCC) and multiple myeloma; condition which has been indicated to be associated with poor disease outcome in several studies [25][26][27][28][29][30][31]. It has been frequently suggested that the increase in Treg cell percentage may provide an immunetolerance toward cancer antigens [32,33].…”
Section: Discussionmentioning
confidence: 99%